The Effect of US Monetary Policy Normalization Toward The Financing Growth of Indonesian Islamic Banking Industry: Short-Term and Long-Term Approaches - Ahmad Mikail; Kenny Devita Indraswari (AFEBI Islamic Finance and Economic Review, 2016)
The study identifies the effect of The Fed Fund Rate (FFR) normalization toward the financing growth of Islamic banks as well as toward the industrial credit growth in Indonesia. To acquire better understanding about the effect of the increasing FFR, Vector Error Correction Model is being utilized in order to identify short run and long run effects. The data employed are the quarterly data of total credit in banking industry, total financing in Islamic banking industry, FFR, real GDP growth, real interest rate, exchange rate and Indonesian composite index from 2003 - 2015. To forecast the dynamic effect of the rising FFR towards financing growth in the Islamic banks, Impulse Response Function is being applied. The result from the long run estimation suggests that the Fed’s monetary policy has negative effect toward the Indonesian banking credit growth as well as the Islamic financing growth. Moreover, the estimated coefficient shows that the effect is quite low in the long run for the conventional bank and relatively high for the Islamic banks. From the short run dynamic analysis, the study reveals that the Islamic banks financing growth is mostly determined by FFR where Islamic financing growth affects Indonesian composite index and real interest rate. However, the Impulse Response Function result exhibits that the Fed’s monetary policy normalization will not affect Islamic banks financing in Indonesia.Keywords: Fed Fund Rate, Financing Growth, Islamic Banking, Indonesia, Monetary Policy